Walking and Dry Season Stresses on Crossbred Cows of Andaman and Nicobar Islands - Perumal, P.; De, A. K.; Bhattacharya, D.; Kundu, A.; Sunder, Jai; Muniswamy, K.; Ravi, S. K.; Bhowmick, Sneha (International Journal of Bio-resource and Stress Management, 2019)
An investigation was carried out to determine the walking stress effect during dry season on physiological, biochemical and heamatological profiles in crossbred cows of Andaman and Nicobar Islands (ANI), India. Twelve numbers of adult crossbred cows of 4-6 yr of age with good body condition (score 5-6) were selected for the experiment. They were categorised into two groups; Group I: control (not exposed to walking stress effect) and Group II: treatment (exposed to walking stress effect) and each group consisted of six animals. In the stress induced group, the cows were walked to 10 km to and fro in the undulated area or hilly areas without allowing grazing from the cattle farm. While control group animals were protected in the separate nearby cattle shed roofed with asbestos sheets with surrounded big trees. The cows walked from 0700 to 1200 h during dry season, i.e. November to February and restrained properly and routine physiological parameters were scaled immediately return from stressful walk during dry season. Similarly blood was collected simultaneously and assessed the routine common heamatological profiles. Antioxidant profiles and lipid peroxide profile were also measured in treatment and control animal groups. Data analysis revealed that physiological, heamatological profiles and also MDA concentration were increased significantly (p<0.05) and concentration of antioxidants were decreased significantly (p<0.05) in the treatment crossbred cows than in control animal group. The study concludes that walking stress during dry season has significantly (p<0.05) influenced the performance of crossbred cows of ANI.